When did recombination suppression events occur in bird ZW sex chromosomes? - Deborah Charlesworth (Nature Communications)
A recent paper found that the sex chromosomes of the crested ibis have more gametolog pairs than many other birds. This Comment discusses that this finding suggets that WZ recombination stopped independently in the sex chromosomes in different bird lineages.